Wind and grid energy-based onshore beach charging station for electric vehicles: An integration infrastructure with techno economics, sustainable mobility, and environmental protection - Anis ur Rehman; Muhammad Fahad Zia; Harism. Khalid; Zafar Said; S.M. Muyeen (Results in Engineering)
The conventional electric vehicle (EV) charging process is often time-consuming, posing a significant challenge in busy schedules. This constraint restricts individuals from engaging in leisure activities like beach picnics, staycations, etc. A combined wind and grid-powered (CWGP) onshore beach charging station (OSBCS) has been proposed to address this issue. It introduces an innovative approach to EV charging that blends sustainable transportation with leisure activities. A detailed case study was carried out at Jumeirah Beach in the United Arab Emirates (UAE), which included 4 charging stations with a combined total of 134 charging slots. The proposed study 1) investigates the relationship between wind speed and variations in power while exploring the unique wind energy production trends, 2) examines the patterns of dynamic grid interaction while highlighting the substantial role of wind power towards integrated charging station energy requirements, and addresses 3) economic factors, 4) patterns of EV charging, and 5) a life cycle assessment (LCA), which enhances the analysis by providing a comprehensive overview of the feasibility and environmental impact of the proposed charging infrastructure. The results show the high potential of the proposed infrastructure to reduce energy costs by nearly 50% through the incorporation of wind energy and lessen carbon emissions by 64% .© 2017 Elsevier Inc. All rights reserved.